Understanding Down Syndrome: A Systematic Review of Genetic, Clinical, and Cognitive Implications - Aluzeib , Abdulmohsen Abdullah; Alshammari , Sultan Nafea; Alshammari, Sattm Ghadwi (Journal of Ecohumanism, 2024)
Down syndrome (DS) is the most common chromosomal disorder, primarily caused by trisomy 21, and is associated with a range of genetic, clinical, and cognitive challenges. This systematic review aims to provide a comprehensive understanding of these aspects by synthesizing recent research on the genetic mechanisms underlying DS, its common clinical manifestations, and the cognitive impairments often observed in affected individuals. Genetic studies highlight the complexity of trisomy 21 and its impact on phenotypic variability. Clinically, DS is associated with distinct physical features, congenital heart defects, and a predisposition to conditions such as thyroid disorders and leukemia. Cognitive impairments, including intellectual disability and early-onset Alzheimer's disease, present significant challenges for individuals with DS, often requiring early intervention and lifelong support. Recent advancements in medical care, therapeutic interventions, and educational strategies have improved quality of life and life expectancy for individuals with DS. This review identifies gaps in the current literature, such as the need for more personalized therapeutic approaches based on genetic variability, and highlights areas for future research to further improve outcomes for individuals with Down syndrome.